Plant awareness and recognition of plants as living beings among biology preservice teachers in Bandung, Indonesia - Puan Helwa Rezha Soraya; Rini Solihat; Riandi Riandi; Taro Harada (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2026)
Humans are highly dependent on the existence of plants; from daily needs to the need to support ecosystems. However, there are some people who are less aware of the existence and importance of plants for life and lead to the phenomenon of plant awareness disparity (PAD). It is important for teachers to have plant awareness and have the awareness that plants are as important as other living things. This study was conducted to reveal the level of PAD of biology pre-service teachers by using PAD-I (Plant Awareness Disparity-Index) developed by Parsley (2022). In addition, this study also explores the recognition of plants as living things in prospective biology teachers by asking them to name living organisms around them. This study used a descriptive cross-sectional method and gathered 35 respondents of biology pre-service teachers from one of the universities in Bandung, Indonesia. The results of the PAD-I score analysis show that preservice biology teachers still have PAD with an average score of 79. In addition, this study also revealed that preservice teachers mostly mentioned living things from the animal kingdom as living things (56%) compared to living things from the kingdom plantae (34%), bacteria (5%), fungi (3%), and protists (2%). From this search, it can be concluded that the biology pre-service teachers still have a tendency to overlook the plant and show a preference for animals. However, there are several approaches that can be taken, such as emphasizing the importance of plants in reducing the impact of climate change and placing plants and animals in the same situation. Through such an approach, it is hoped that students will develop an awareness of plants as a first step toward plant conservation, particularly with native Indonesian plants.